Efficacy, durability, and tolerability of dolutegravir/lamivudine and dolutegravir/rilpivirine for the treatment of HIV in a real‐world setting in Belgium. Issue 3 (8th August 2022) - Nasreddine, Rakan; Yombi, Jean Cyr; Darcis, Gilles; Florence, Eric; Allard, Sabine D.; De Scheerder, Marie‐Angélique; Henrard, Sophie; Demeester, Rémy; Messiaen, Peter; Ausselet, Nathalie; Loeckx, Matthias; Delforge, Marc; et al.
Abstract: Objectives: A paradigm shift from three‐drug regimens to two‐drug regimens (2DRs) is currently taking place in real‐world clinical practice. This study aimed to describe the efficacy, durability, and tolerability of dolutegravir (DTG)/lamivudine (3TC) and DTG/rilpivirine (RPV) in a real‐world setting. Methods: This was a retrospective, observational, multicentre (ten centres in Belgium) study involving adult treatment‐naïve and treatment‐experienced people living with HIV on DTG/3TC or DTG/RPV between 1 January 2019 and 30 September 2020. The primary endpoint was rate of virological suppression (VS; plasma HIV‐1 viral load [VL] <50 copies/ml) using an on‐treatment analysis. Main secondary endpoints included the proportion of people that experienced loss of VS (LVS; defined as two consecutive HIV‐1 VLs of >200 copies/ml after initially achieving VS) and a resistance analysis at the time of LVS; rate, incidence, and reasons for discontinuation of treatment (stopping treatment or changing any component of the 2DR); and change in weight, along with the proportion of people reporting a >10% weight gain. Ordinal logistic regression analysis examined associations between baseline variables and >10% on‐treatment weight gain. Results: Overall, 948 people were included, of whom 734 (77%) were on DTG/3TC and 214 (23%) were on DTG/RPV. Baseline characteristics included 54% aged ≥50 years, 31% female, 31% Black sub‐Saharan African, 95% treatment‐experienced, and 8% with HIV‐1 VL ≥50 copies/ml. Through 48 weeks, the rate of VS for the overall cohort was 98.3% (99.1% with 3TC; 96.2% with RPV). LVS was observed in 0.5% ( n = 5) of the overall population ( n = 1 [3TC group], n = 4 [RPV group]). There were 40 treatment discontinuations (4.2%, n = 27 [3TC group]; n = 13 [RPV group]), corresponding to an incidence of 4.7 per 100 patient‐years. The most common reason for discontinuation was an adverse event (1.4%), with neurotoxicity the most frequent (0.5%). Median on‐treatment weight gain at week 48 was 1 kg (interquartile range [IQR] −1–3) overall, 1 kg (IQR −1–3) in the 3TC group, and 2 kg (IQR 0–4) in the RPV group. A >10% weight increase was observed in 6.3% of people. Regression analysis showed that being on a tenofovir disoproxil fumarate‐based regimen prior to 2DR initiation was the only variable associated with a >10% increase in weight from baseline (odds ratio 3.48; 95% confidence interval 1.13–10.68; p = 0.038). Conclusion: In this real‐world analysis, the 2DRs analysed were effective, durable, and safe for those who were treatment‐naive and treatment‐experienced. A slight increase in weight was associated with these regimens.